Dynamics Of Communication and Community Readiness Using The Population Service Application 'Dukcapil Ceria Mobile' Disdukcapil Padang Pariaman Regency - Ahady, Yazhra Azmi; Chatra, Emeraldy; Asrinaldi, Asrinaldi (Hulondalo Jurnal Ilmu Pemerintahan dan Ilmu Komunikasi, 2025)
This research aims to analyze the dynamics of communication and community readiness in using the Dukcapil Ceria Mobile application in Padang Pariaman Regency. This innovation was carried out by the Padang Pariaman Regency Population and Civil Registration Service (Disdukcapil) in initiating e-government at the regional level by releasing the Dukcapil Ceria Mobile (DCM) population service application since 2019. This application is used to increase efficiency, transparency and accessibility of population services. This research uses qualitative methods with a constructivist paradigm and a case study approach. Data was collected through in-depth interviews, observation and documentation. The research results show that the communication dynamics that occur show a shift from conventional to digital methods, where various communication channels are used to socialize the benefits and use of this application. Effective communication strategies through mass media, social media and grassroots methods have succeeded in disseminating information about DCM applications quickly and widely, increasing public understanding and interest. Overall community readiness in using the DCM application is quite good, although some individuals experience obstacles related to limited internet access and technical support. This research also found that the DCM application was successful in increasing the efficiency and accessibility of population services, as well as minimizing the costs and time needed by the public to process population documents. However, to achieve wider and more comprehensive adoption, ongoing socialization is needed from the government and related stakeholders. Penelitian ini bertujuan untuk menganalisis dinamika komunikasi dan kesiapan masyarakat dalam menggunakan aplikasi Dukcapil Ceria Mobile di Kabupaten Padang Pariaman. Inovasi ini dilakukan oleh Dinas Kependudukan dan Pencatatan Sipil (Disdukcapil) Kabupaten Padang Pariaman dalam menginisiasi e-government pada pemerintahan tingkat daerah dengan merilis aplikasi layanan kependudukan Dukcapil Ceria Mobile (DCM) sejak tahun 2019 lalu. Aplikasi ini digunakan untuk meningkatkan efisiensi, transparansi, dan aksesibilitas layanan kependudukan. Penelitian ini menggunakan metode kualitatif dengan paradigma konstruktivis dan pendekatan studi kasus. Data dikumpulkan melalui wawancara mendalam, observasi, dan dokumentasi. Hasil penelitian menunjukkan bahwa dinamika komunikasi yang terjadi memperlihatkan pergeseran dari metode konvensional ke digital, dimana berbagai saluran komunikasi digunakan untuk mensosialisasikan manfaat dan penggunaan aplikasi ini. Strategi komunikasi yang efektif melalui media massa, media sosial dan metode grassroot berhasil menyebarkan informasi mengenai aplikasi DCM dengan cepat dan luas, meningkatkan pemahaman serta minat masyarakat. Kesiapan masyarakat secara keseluruhan dalam menggunakan aplikasi DCM cukup baik, meskipun beberapa individu mengalami hambatan terkait keterbatasan akses internet dan dukungan teknis. Penelitian ini juga menemukan bahwa aplikasi DCM berhasil meningkatkan efisiensi dan aksesibilitas layanan kependudukan, serta meminimalisir biaya dan waktu yang dibutuhkan masyarakat dalam mengurus dokumen kependudukan. Namun, untuk mencapai adopsi yang lebih luas dan menyeluruh, diperlukan sosialisasi yang berkelanjutan dari pihak pemerintah dan stakeholder terkait.